2013
DOI: 10.1002/smll.201202317
|View full text |Cite
|
Sign up to set email alerts
|

A Trachea‐Inspired Bifurcated Microfilter Capturing Viable Circulating Tumor Cells via Altered Biophysical Properties as Measured by Atomic Force Microscopy

Abstract: Circulating tumor cells (CTCs), though exceedingly rare in the blood, are nonetheless becoming increasingly important in cancer diagnostics. Despite this keen interest and the growing number of potential clinical applications, there has been limited success in developing a CTC isolation platform that simultaneously optimizes recovery rates, purity, and cell compatibility. Herein, a novel tracheal carina-inspired bifurcated (TRAB) microfilter system is reported, which uses an optimal filter gap size satisfying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…Similar positive findings by size-based CTC isolation were reported in melanoma [162][163][164], gastric cancer [76,165], prostate cancer [166,167], lung cancer [168][169][170], pancreatic cancer [103], liver cancer [127], sarcoma [171], and breast cancer [172]. Separation by physical properties, i.e., gravity, density gradients, using microfluidic technology [45,46,56,60,[173][174][175][176][177][178][179][180][181][182][183][184][185][186], or microfiltration [53,172,187,188] were also reported to be able to capture CTCs efficiently.…”
Section: Label-free Isolation Strategysupporting
confidence: 73%
“…Similar positive findings by size-based CTC isolation were reported in melanoma [162][163][164], gastric cancer [76,165], prostate cancer [166,167], lung cancer [168][169][170], pancreatic cancer [103], liver cancer [127], sarcoma [171], and breast cancer [172]. Separation by physical properties, i.e., gravity, density gradients, using microfluidic technology [45,46,56,60,[173][174][175][176][177][178][179][180][181][182][183][184][185][186], or microfiltration [53,172,187,188] were also reported to be able to capture CTCs efficiently.…”
Section: Label-free Isolation Strategysupporting
confidence: 73%
“…Also, there is less chance that a CTC will slip through the filter. Simulations showed that the fluidic pressure was almost 10 times less exerted in the microslit approach (Fig 4A) when comparing to a filter with 8 μm gaps spaced 100 μm apart (Fig 4B), which was modeled with similar geometry condition of the previous filter studies [23, 24]. In addition, as the number of captured cells increases, the tendency was not changed and more pressure increase on the cell membrane was exhibited in the filter type (Fig 4C and 4D).…”
Section: Resultsmentioning
confidence: 93%
“…In addition to size amplification, binding microparticles to cancer cells may also increase the stiffness of these cells, which has been confirmed by using the atomic force microscopy nanoindentation . Based on this principle, a tracheal carina‐inspired bifurcated microfilter and a Parsortix™‐like trapping pillar array were employed to isolate MCF‐7 cells coated with immunoparticles from whole blood samples with high efficiency and purity. To facilitate the labeling processes of CTCs, a microfluidic mixer composed of wavy ducts with sharp‐edged turns was fabricated to generate Taylor–Gortler vortex flows, which improve the interactions between cancer cells and anti‐EpCAM conjugated microbeads .…”
Section: Physical Cell Sorting Enhanced By Biochemical Principlesmentioning
confidence: 92%